OPTIMIZATION OF UPDATING LAND AND BUILDING TAX OBJECT IN IMPROVING LOCAL OWN-SOURCE REVENUE FOR MEDAN DEVELOPMENT ACCELERATION - Siahaan, Elisabet; Fachruddin, Khaira Amalia; Fachruddin, Hilma Tamiami (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2018)
Local own-source revenue is one of the sources of revenue for the government of Medan. This revenue is used to accelerate the development of the city of Medan, especially in the infrastructure development section. A better infrastructure will help in the implementation of business operations that support the improvement of community welfare. One source of local revenues is the local tax revenue. The community service was conducted to optimize the revenue of Medan through optimizing the value of taxable object. This community service supported the government of Medan medium term plan program. This service was carried out with briefing methods, workshops, and mentorings. Science and technology given include work ethic, effective communication, and taxable object valuation. The results of this community service were satisfactory. There was a significant change in the attitude of partners while updating the data. As the results, the community as the owner of taxable object becomes more cooperative and the updating data goes better.